Nursesâ€™ Patient Safety Competencies in Aceh Province, Indonesia - Julianto, Rahmad; Thiangchanya, Pratyanan; Boonyoung, Nongnut (Department of Nursing, Faculty of Medicine, Diponegoro University, 2014)
Purpose: To determine the level of nursesâ€Ÿ patient safety competencies in Aceh, Indonesia.Methods: A descriptive study was conducted to randomly recruit 207 nurses in a hospital in Banda Aceh, Indonesia. The nursesâ€Ÿ patient safety competencies was measured by using the Patient Safety Competencies of Nurses Questionnaire (PSCNQ) which was a self-reported, 29-item questionnaire rated on a 4-point Likert scale (1 to 4), developed based on the Canadian Patient Safety Instituteâ€Ÿs Safety Competencies. Result: More than half of nurses participated in the study were less than 30 years old, with a mean age of 31 years. The majority was female, married, earned diploma degree, and had working experience of 1-10 years. The overall nursesâ€Ÿ patient safety competencies was at a high level. The area that nurses reported highest competency was â€œuse personal protective equipmentâ€. Whereas the area they reported lowest competency was â€œmaintain the documents of adverse events and report each adverse event.â€Conclusion: The study findings suggested that Acehnese nurse leaders should further maintain and promote nursesâ€Ÿ patient safety competencies. Studies exploring factors contributing to nursesâ€Ÿ patient safety competencies together with utilizing other data collection methods, such as observation is worth investigated.